Acute mesenteric venous thrombosis after laparoscopic sleeve gastrectomy: a case report and a literature review - Sedik, Alaa; Aleashed, Fawaz; Fathi, Ahmed (International Surgery Journal, 2019)
Over the last decade, laparoscopic sleeve gastrectomy has become an increasingly popular surgical procedure for morbid obesity. Moreover, post-laparoscopic sleeve gastrectomy mesenteric venous thrombosis is very rarely reported. The presentation varies from mild non-speciﬁc abdominal symptoms to life threatening surgical emergency. Superior mesenteric vein thrombosis after bariatric surgery is a difficult diagnosis that needs a high index of suspicion. We report a case of thrombosis of the superior mesenteric vein, who presented as acute emergency to emergency room, shortly after sleeve gastrectomy. Patient underwent laparotomy and offered a resection of 60 cm of infarcted proximal jejunum with restoration of bowel continuity later. Patient subsequently recovered and followed several times in our outpatient and was free of symptoms.